Reinventing the Wheel and Making It Round Again: Evolutionary Convergence in Buchnera–Serratia Symbiotic Consortia between the Distantly Related Lachninae Aphids Tuberolachnus salignus and Cinara cedri - Manzano-Marín, Alejandro (Genome Biol Evol, 2016)
Virtually all aphids (Aphididae) harbor Buchnera aphidicola as an obligate endosymbiont to compensate nutritional deficiencies arising from their phloem diet. Many species within the Lachninae subfamily seem to be consistently associated also with Serratia symbiotica. We have previously shown that both Cinara (Cinara) cedri and Cinara (Cupressobium) tujafilina (Lachninae: Eulachnini tribe) have indeed established co-obligate associations with both Buchnera and S. symbiotica. However, while Buchnera genomes of both Cinara species are similar, genome degradation differs greatly between the two S. symbiotica strains. To gain insight into the essentiality and degree of integration of S. symbiotica within the Lachninae, we sequenced the genome of both Buchnera and S. symbiotica endosymbionts from the distantly related aphid Tuberolachnus salignus (Lachninae: Tuberolachnini tribe). We found a striking level of similarity between the endosymbiotic system of this aphid and that of C. cedri. In both aphid hosts, S. symbiotica possesses a highly reduced genome and is found exclusively intracellularly inside bacteriocytes. Interestingly, T. salignus’ endosymbionts present the same tryptophan biosynthetic metabolic complementation as C. cedri’s, which is not present in C. tujafilina’s. Moreover, we corroborate the riboflavin-biosynthetic-role take-over/rescue by S. symbiotica in T. salignus, and therefore, provide further evidence for the previously proposed establishment of a secondary co-obligate endosymbiont in the common ancestor of the Lachninae aphids. Finally, we propose that the putative convergent split of the tryptophan biosynthetic role between Buchnera and S. symbiotica could be behind the establishment of S. symbiotica as an obligate intracellular symbiont and the triggering of further genome degradation.